Beyond the hospital walls: ORL-HNS steps into the community again - Din, Sobani; Mohamad Fuzi, Noor Shahira (Faculty of Medicine, 2025)
On 14 June 2025, the Department of Otorhinolaryngology Head and Neck Surgery (ORL HNS), Hospital Al- Sultan Abdullah (HASA), in collaboration with the Faculty of Medicine, Universiti Teknologi MARA (UiTM), successfully organised the fourth annual community service programme, led by Dr. Sobani Din. The previous success of similar initiatives held in Bukit Badong, Puncak Alam Housing Sdn. Bhd, and Sekolah Menengah Kebangsaan Saujana Utama highlighted both the effectiveness of the programme and the ongoing need to reach out to more communities. This year, the programme was extended to Sekolah Kebangsaan (SK) Seri Pristana.